Family support in cervical cancer patients treated: A qualitative case study - Dwi Kurniasih; Elly Marce Titihalawa; Septiani Vivin Rahayu Tiningsih (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Cervical cancer not only has the potential to cause physical suffering but also causes psychological suffering. Considering the negative impact of cervical cancer, cervical cancer sufferers need family support. Family support is the attitude, actions and acceptance of the family towards a sick family member. Family attention is very helpful in choosing the health of his family.Purpose: To determine the impact that cervical cancer patients receive when they receive family support.Method: Qualitative research with a case study research strategy. Data collection was carried out through semi-structured interviews involving three participants. The data is then subjected to domain analysis.Results: In this research, 2 themes were found, namely, knowing the support provided by the family and knowing the impact felt by the patient when receiving family support.Conclusion: Family support is very important for cervical cancer patients undergoing the treatment process, because it will have an impact that will be felt by the patient later. The impact is felt like the patient feels cared for, given appreciation, loved and feels owned by his family. so that the patient has the motivation to recover and has confidence in worrying about the disease they are suffering from.